Improved Monitoring of Low-Level Transcription in Escherichia coli by a β-Galactosidase α-Complementation System - Guo, Yan; Hui, Chang-Ye; Liu, Lisa; Zheng, Hao-Qu; Wu, Hong-Min (Frontiers in Microbiology, 2019)
Genetically encoded reporter proteins are important and widely used tools for the identification and capture of a promoter, tracking the dynamic behavior of transcription, and the quantification of promoter activity. The sensitivity of the reporter gene is a critical factor for an ideal reporter system because weak transcriptional signal has usually failed to be detected using classical reporters. In this study, we present a novel reporter system for improved monitoring of transcription in E. coli based on β-galactosidase α-complementation. In this reporter system, the β-galactosidase activity resulting from the assembly of a reporter lacZα and an existing α-acceptor in advance serves as a measure of transcriptional activity in vivo. To validate the potential of the lacZα-derived reporter system, a series of artificial operons were constructed, and the moderately strong lac promoter, ara promoter, and weak pbr promoter were chosen as the detection promoters. The response profiles of lacZα was similar to that of wild type lacZ in artificial lac operons. Due to its small size and efficient expression profile, the detection sensitivity of a lacZα-derived reporter system was significantly higher than that of the traditional full-length β-galactosidase and the fluorescent protein mCherry reporter system in artificial ara operons. As expected, the response sensitivity of the lacZα-derived reporter system was also demonstrated to be significantly higher than that of the β-galactosidase and mCherry reporter systems in lead-sensitive artificial pbr operons. The lacZα-derived reporter system may prove to be a valuable tool for detecting promoter activity, especially low-level transcription in vivo.